Beberapa aspek biologi reproduksi ikan siro (Sardinella longiceps Val.) di Perairan Teluk Kendari, Sulawesi Tenggara [Reproductive biology aspects of indian oil sardine in Kendari Bay, Southeast Sulawesi] - Asriyana Asriyana; La Sara (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2013)
The research on reproductive biology of Indian oil sardine was carried out from October to December 2012 in Kendari Bay, Southeast Sulawesi. The objective of this research was to describe aspects of the reproductive biology of Indian oil sardine such as sex ratio, gonadal maturation, gonadosomatic index, fecundity, and length at first maturity (Lm50). Fish collection was done using experimental gillnets (with different mesh sizes of %, 1, 1%, and 1% inches). The gonadal maturation of fish was determined morphologically by comparing the shape, size, color, and gonad weight. A total of 1794 individual fish were caught with ranging 88-216 mm in length and 5.7- 30.4g in weight. The sex ratio of female was more dominant than the male. The gonadosomatic index of male and female were higher at Zone III (4.32±4.33 and 5.03±5.04) and in December (4.11±1,32 and 5.14±1.6), while length at first maturity (Lm50) of female and male were 122-132 mm. Fecundity of fish in weight of 9.8-30.4 g were varied from 501 to 17,446. Abstrak Penelitian biologi reproduksi ikan siro (Sardinella longiceps Val.) di perairan Teluk Kendari dilakukan dari Oktober sampai Desember 2012. Penelitian ini bertujuan untuk menganalisis beberapa aspek biologi reproduksi ikan siro, me-liputi nisbah kelamin, kematangan gonad, indeks kematangan gonad, fekunditas, dan ukuran pertama kali matang gonad. Koleksi ikan dilakukan dengan jaring insang eksperimental (ukuran mata jaring berbeda %, 1, 1 %, 1 %, dan 2 inci). Kematangan gonad ikan diamati secara morfologi dengan melihat bentuk, ukuran, warna, and bobot gonad. Se-lama penelitian diperoleh 1.794 ekor ikan siro dengan kisaran panjang dan bobot masing-masing 88-216 mm dan 5,730,4 g. Ikan siro betina lebih dominan daripada ikan jantan. Rata-rata indeks kematang-an gonad ikan jantan dan betina terbesar ditemukan pada Zona III (4,32±4,33 dan 5,03±5,04) dan pada bulan Desember (4,11±1,32 dan 5,14±1,6). Ikan pertama kali matang gonad ditemukan pada ukuran 122-132 mm. Fekunditas ikan betina matang gonad dengan bobot tubuh 9,8-30,4 g berkisar 501-17.446 butir.